2021
DOI: 10.1186/s41118-021-00135-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 lockdown on university students’ anxiety disorder in Italy

Abstract: The COVID-19 pandemic has highlighted the vulnerability of specific population sections, with regards to economic and work conditions, mental and physical well-being, and context-based factors, emphasizing the need for timely policy measures aimed at counteracting the Italian economic framework’s fragility—which poorly adapts to unexpected circumstances. Identifying the most vulnerable groups is, therefore, essential with a view to carrying out targeted measures. Concerning University, the economic downturn ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…The result that females compared with males, among undergraduate students, worsened their mental health status more, is in line with current national and international COVID-19 literature that estimates a greater risk in females than males in developing depression, anxiety, paranoid ideations, posttraumatic stress symptoms, sleep disorders, and a worsening in the interpersonal sensitivity dimension (13,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 84%
“…The result that females compared with males, among undergraduate students, worsened their mental health status more, is in line with current national and international COVID-19 literature that estimates a greater risk in females than males in developing depression, anxiety, paranoid ideations, posttraumatic stress symptoms, sleep disorders, and a worsening in the interpersonal sensitivity dimension (13,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 84%
“…These results corroborate the pattern of relationships among motivational aspects found in the aforementioned studies. Moreover, in line with the literature, they confirm the negative impact of the COVID-19 crisis on the well-being of students who more frequently reported higher levels of anxiety (e.g., Busetta et al, 2021 ). Together these findings suggest that an intervention aimed to promote internal causal attributions and reduce dysfunctional beliefs by modulating anxiety and resilience may effectively support students.…”
Section: Discussionsupporting
confidence: 88%
“…A second study conducted a month later in Malaysia during the COVID-19-related online teaching found that more than half of university students showed moderate to severe anxiety [16]. Busetta et al also investigated the anxiety levels among Italian university students during the period of COVID-19-related lockdown [17]. The study showed that high anxiety levels were reported by >50% of the university students, and >50% of the students started to experience anxiety, while >60% of the students who suffered from anxiety before the pandemic showed aggravated anxiety symptoms during the pandemic [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Woon et al reported that after the movement control order was lifted in Malaysia, and some strict social activities were resumed, 36.4%, 36.7%, and 42.4% of the university students experienced mild to extremely severe levels of depression, anxiety and stress, respectively [19]. The previous studies evaluating the impact of COVID-19 on the mental health of university students revealed that several factors, such as infected friends or relatives, quarantine, lockdown, financial problems, wearing masks, checking temperature routinely, female gender, online learn-ing, and ambiguity of the future, are associated with a higher risk for developing mental disorders [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%